Reduced Influenza B–Specific Postvaccination Antibody Cross-reactivity in the B/Victoria Lineage–Predominant 2019/20 Season. (29th September 2020) - Xie, Hang; Xiang, Ruoxuan; Wan, Hamilton J; Plant, Ewan P; Radvak, Peter; Kosikova, Martina; Li, Xing; Zoueva, Olga; Ye, Zhiping; Wan, Xiu-Feng
Abstract: Background: The influenza activity of the 2019/20 season remained high and widespread in the United States with type B viruses predominating the early season. The majority of B viruses characterized belonged to B/Victoria (B/Vic) lineage and contained a triple deletion of amino acid (aa) 162–164 in hemagglutinin (3DEL). These 3DEL viruses are antigenically distinct from B/Colorado/06/2017 (CO/06)—the B/Vic vaccine component of the 2018/19 and 2019/20 seasons representing the viruses with a double deletion of aa 162–163 in hemagglutinin (2DEL). Methods: We performed molecular characterization and phylogenetic analysis of circulating B/Vic viruses. We also conducted hemagglutination inhibition (HAI) assay using archived human postvaccination sera collected from healthy subjects administered with different types of 2018/19 or 2019/20 seasonal vaccines. Their HAI cross-reactivity to representative 3DEL viruses was analyzed. Results: The CO/06-specific human postvaccination sera, after being adjusted for vaccine type, had significantly reduced HAI cross-reactivity toward representative 3DEL viruses, especially the 136E+150K subgroup. The geometric mean titers against 3DEL viruses containing 136E+150K mutations were 1.6-fold lower in all populations ( P = .051) and 1.9-fold lower in adults ( P = .016) compared with those against the 136E+150N viruses. Conclusions: Our results indicate that postvaccination antibodies induced by the B/Vic vaccine component of the 2019/20 influenza season had reduced HAI cross-reactivity toward predominant 3DEL viruses in the United States. A close monitoring of the 3DEL 136E+150K subgroup is warranted should this subgroup return and predominate the 2020/21 influenza season. Abstract : The US 2019/20 influenza season had a B/Victoria vaccine component different from circulating V1A.3 viruses containing a triple amino acid deletion (3DEL) in hemagglutinin. Human postvaccination sera showed reduced hemagglutination inhibition cross-reactivity toward the 3DEL viruses, especially those containing additional 136E+150K mutations.